Power amplifier PAE and ruggedness optimization by second-harmonic control. - Spirito, M. (IEEE Journal of solid state circuits)
Second-harmonic control is applied to optimize power-added efficiency (PAE) and ruggedness of silicon power amplifiers (PAs). A differential push-pull topology is chosen because it facilitates independent fundamental load and second-harmonic control. Various amplifiers using high-Q passives for fundamental and harmonic matching have been implemented. Experiments demonstrated an increase in PAE and ruggedness simultaneously even under high mismatch conditions. The amplifiers are operating in class-AB and are intended for use in the digital communication system (DCS) band.